Evaluation of Liposome-Loaded Microbubbles as a Theranostic Tool in a Murine Collagen-Induced Arthritis Model - Joke Deprez; Silke Roovers; Guillaume Lajoinie; Heleen Dewitte; Tine Decruy; Julie Coudenys; Benedicte Descamps; Christian Vanhove; Michel Versluis; Dirk Elewaut; Peggy Jacques; Stefaan C. De Smedt; et al. (MDPI AG, 2022)
Rheumatoid arthritis (RA) is an autoimmune disease characterized by severe inflammation of the synovial tissue. Here, we assess the feasibility of liposome-loaded microbubbles as theranostic agents in a murine arthritis model. First, contrast-enhanced ultrasound (CEUS) was used to quantify neovascularization in this model since CEUS is well-established for RA diagnosis in humans. Next, the potential of liposome-loaded microbubbles and ultrasound (US) to selectively enhance liposome delivery to the synovium was evaluated with in vivo fluorescence imaging. This procedure is made very challenging by the presence of hard joints and by the limited lifetime of the microbubbles. The inflamed knee joints were exposed to therapeutic US after intravenous injection of liposome-loaded microbubbles. Loaded microbubbles were found to be quickly captured by the liver. This resulted in fast clearance of attached liposomes while free and long-circulating liposomes were able to accumulate over time in the inflamed joints. Our observations show that murine arthritis models are not well-suited for evaluating the potential of microbubble-mediated drug delivery in joints given: (i) restricted microbubble passage in murine synovial vasculature and (ii) limited control over the exact ultrasound conditions in situ given the much shorter length scale of the murine joints as compared to the therapeutic wavelength.